Pelatihan Pengembangan Soal Hots Materi Pembelajaran Sejarah Tingkat SMA Sederajat di Kabupaten Indragiri Hulu - Bunari, Bunari; Alfiqri, Yanuar; Nurdiansyah, Nurdiansyah; Bakara, Refli Surya (Universitas Indraprasta PGRI, 2023)
The purpose of this service initiative is to enhance the knowledge and proficiency of High School and Equivalent Teachers in the Indragiri Hulu Regency. This is achieved through a Training Program focused on Developing Higher Order Thinking Skills (HOTS) Questions for History Learning Materials at the High School and Equivalent Levels in Indragiri Hulu Regency. The instructional methods employed encompass lectures, question and answer sessions, trials/simulations, and workshops. The training outcomes indicate the successful realization of the objectives. This is evidenced by the enthusiastic participation of the training attendees during discussions and the positive results of assignments given by the presenters. These outcomes demonstrate an observable improvement in teachers' understanding and capacity to incorporate HOTS into learning outcomes questions.